Analisis Pengaruh Fundamental Makro, Kebijakan Deviden, Keputusan Pendanaan, Keputusan Investasi, Terhadap Nilai Perusahaan Dengan Kinerja Keuangan & Struktur Kepemilikkan sebagai Variabel Intervening Pada Perusahaan Sektor Industrial Yang Terdaftar di BEI Tahun 2018-2023 - Joshua Yonathan Sugianto; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to analyze whether macro fundamentals, dividend policy, funding decisions and investment decisions influence company value with financial performance and ownership structure as intervening variables. The method used in the research is quantitative with secondary data sources originating from the 2018-2023 financial reports. The population in the research are companies listed on the Indonesian Stock Exchange, while the sampling technique used in the research uses purposive sampling where 5 industrial companies are selected by researchers with certain criteria. The tool for processing and analyzing data uses the Smart-Pls version 4 application. Analysis results shows that macro fundamentals, dividend policy and investment decisions do not have a direct effect on the company's financial performance, while funding decisions have an effect on the company's financial performance; Macro fundamentals, investment decisions, funding decisions do not influence the ownership structure, while dividend policy influences the ownership structure; Ownership structure has an insignificant influence on financial performance, financial performance has a negative and significant influence on company value, ownership structure has a positive and significant influence on company value.